MRI findings before and after prolapse surgery: $hCéline D. Alt, Kerstin A. Brocker, Florian Lenz, Christof Sohn, Hans-Ulrich Kauczor and Peter Hallscheidt - Alt, Céline D.; Brocker, Kerstin A.; Lenz, Florian; Sohn, Christof; Kauczor, Hans-Ulrich; Hallscheidt, Peter (Acta radiologica, 2014)
Background: Therapeutical outcome after prolapse surgery is evaluated using a standardized grading system based onmaximum prolapse extent, which might not provide the full picture of the patient’s subjective outcome. We thereforeapplied an evaluation method, which is detached from a grading system.
Gesehen am 08.09.2020